2018
DOI: 10.2147/dddt.s164565
|View full text |Cite
|
Sign up to set email alerts
|

Positives and negatives of nonsteroidal anti-inflammatory drugs in bone healing: the effects of these drugs on bone repair

Abstract: Tissue damage following injury triggers the processes of coagulation, inflammation and healing. In tissues surrounding the bone, the result of the healing process is a scar, while bone tissue has a unique ability to achieve shape, strength and pre-injury function. Bone healing is a process of regeneration rather than classic recovery. The result of this process is the formation of new, healthy bone tissue instead of a scar. Many factors can inhibit or impair the bone healing process, and their influence is cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 46 publications
1
65
0
4
Order By: Relevance
“…NSAIDs and coxibs, which inhibit the production of PGH2 from arachidonic acid, are used to treat pain and inflammation after tendon injury. However, many studies have shown that the use of these drugs reduces or delays tendon healing (Ferry et al, 2007;Dimmen et al, 2009;Hammerman et al, 2015), which is similar to observations in other musculoskeletal tissues (Cohen et al, 2006;Su & O'Connor, 2013;Dueweke et al, 2017;Lisowska et al, 2018). PGH2 is metabolized by specific synthases to produce other prostaglandins, such as PGD2, PGE2, PGF2α, and PGI2, that modulate inflammation (Trappe & Liu, 2013).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…NSAIDs and coxibs, which inhibit the production of PGH2 from arachidonic acid, are used to treat pain and inflammation after tendon injury. However, many studies have shown that the use of these drugs reduces or delays tendon healing (Ferry et al, 2007;Dimmen et al, 2009;Hammerman et al, 2015), which is similar to observations in other musculoskeletal tissues (Cohen et al, 2006;Su & O'Connor, 2013;Dueweke et al, 2017;Lisowska et al, 2018). PGH2 is metabolized by specific synthases to produce other prostaglandins, such as PGD2, PGE2, PGF2α, and PGI2, that modulate inflammation (Trappe & Liu, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…Nonsteroidal antiinflammatory drugs (NSAIDs) and COX-2 inhibitors (coxibs) have been used clinically to treat pain and prevent inflammation after tendon repair, but in most cases the use of NSAIDs or coxibs reduces or delays tissue healing (Ferry et al, 2007;Dimmen et al, 2009;Hammerman et al, 2015). This is true not only for tendon, but also for other musculoskeletal tissues including skeletal muscle, bone, and the enthesis (Cohen et al, 2006;Su & O'Connor, 2013;Dueweke et al, 2017;Lisowska et al, 2018). NSAIDs and coxibs block the production of prostaglandin H2 (PGH2) from arachidonic acid, and PGH2 is a precursor for the production of several prostaglandins including PGD2, PGE2, PGF2α, and PGI2 (Trappe & Liu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…И.М. Сеченова» Минздрава России (Сеченовский Университет), кафедра ревматологии Института профессионального образования, Москва, Россия; 3 ГБУЗ «Городская клиническая больница №68» Департамента здравоохранения г. Москвы, Москва, Россия; 4 БУЗ УР «Республиканский клинико-диагностический центр», Ижевск, Россия; 5 КГБУЗ «Красноярская межрайонная поликлиника №1», Красноярск, Россия; 6 ГУЗ «Городская поликлиника №11», Саратов, Россия; 7 ГАУЗ ПК «Городская клиническая больница №3», Пермь, Россия; 8 Нестероидные противовоспалительные препараты (НПВП) -один из основных классов фармакологических средств, используемых для лечения ревматических заболеваний (РЗ). Прежде всего НПВП рассматриваются как средство для терапии боли и локального воспаления, сопровождающих поражение суставов, позвоночника и околосуставных мягких тканей.…”
unclassified
“…Кроме этого, НПВП оказывают существенное влияние на развитие воспалительной реакции, снижая экспрессию гена ЦОГ2 и опосредованно влияя на экспрессию генов ряда интерлейкинов (ИЛ) -ИЛ1, ИЛ6, фактора некроза опухоли α, синтез факторов роста, активацию клеток макрофагального ряда, в том числе остеокластов. Способность этих препаратов оказывать локальное и системное противовоспалительное действие, замедлять развитие неоангиогенеза, гетеротопической оссификации и рост остеофитов (процессов, определяющих необратимые структурные изменения суставов и позвоночника), позволяет рассматривать длительное использование НПВП как рациональный подход для патогенетической терапии определенных нозологических форм и субтипов РЗ [1,[2][3][4][5].…”
unclassified
See 1 more Smart Citation